Penataan dan Pembuatan Nomor Rumah pada Kegiatan Kuliah Kerja Nyata di Desa Sampurna - Febriyandi, Febriyandi; Febriani , Julia; Karimah, Karimah; Fajri, Muhammad; Rizal, Muhammad; Nordiana, Nordiana; Safitri, Novia; Asiah, Nur; Huda, Nurul; Wirdan, Wirdan (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
KKN or Real Work Lectures is a program implemented by universities as a form of implementation of the Tri Dharma of higher education. Students in KKN activities interact directly with the community and help solve problems in the village. One of the problems found in Sampurna Village is the lack of house identification, namely house numbers, in all residents' houses. The number of residential houses in Sampurna Village is 212 houses. Houses that don't have numbers will have impacts such as making it difficult for village officials to register residents' houses and making it difficult for village and non-village residents to find out the exact address of a house because it doesn't have a clear identity. Therefore, this program for arranging and creating house numbers was carried out as a KKN activity to help the residents of Sampurna Village so that their houses have a clear identity. In this activity, 212 house numbers were produced which were installed directly into the homes of Sampurna Village residents.  The existence of this resident's house number can become a house identity which is expected to help village officials in collecting data and make it easier for all parties to find the location of residents' home addresses